Effect of annealing temperature for structural, electrical, and ammonia sensing properties of pristine ZnO and ZnO/SiO2 nanoparticles - Chaiyo, Pitchanunt; Dokden, Kewalin; Thumthan, Orathai; Sumran, Supon (Indochina Applied Sciences, 2024)
The main objective of this research was to study the electrical and gas-sensing properties of Zinc oxide (ZnO) nanoparticles. The samples were divided into two conditions in the preparation process. In the first condition, ZnO powder was annealed at temperatures of 650, 700, and 750 ๐C for 2 h, while the second condition involved mixing ZnO powder with SiO2 powder and annealing at temperatures of 650, 700 and 750 ๐C for 2 h. The characteristics of the prepared samples were studied by scanning electron microscopy (SEM) and the X-ray diffraction technique (XRD). The SEM images showed the agglomeration of the particles with micron-sized diameters. In addition, the XRD patterns of all samples exhibited the hexagonal structure of ZnO. Assessment of the electrical properties of the samples was carried out by forward bias from 0 – 15 V and reverse bias from 0 V to -15 V. The I – V characteristic curves showed diode-like rectifying behavior.The gas-sensing property of the samples was investigated by using ammonia gas, and ZnO nanoparticles annealed at 750 ºC for 2 h were found to have the highest sensitivity.